Questions from Our Readers Commentary on Lamaze International's Statement on Induction - Lothian, Judith A. (2001)
Lamaze International recommends that “pregnant women neither choose nor agree to be induced unless there is a true medical indication for induction.” This commentary discusses the recommendation and its implications for the practice of childbirth education.